2020
DOI: 10.1089/acm.2019.0455
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of T'ai Chi for Older Adults with Chronic Back Pain: A Qualitative Study

Abstract: Objective: To determine the perceived benefits of t'ai chi in older adults with chronic low-back pain (cLBP). Design: A qualitative analysis from a randomized controlled feasibility trial. Subjects: Eighteen participants (65+ years old) with cLBP of at least moderate intensity. Intervention: A 36-week intervention beginning with twice weekly classes for 12 weeks, weekly classes for 6 weeks, biweekly classes for 6 weeks, and monthly classes for 12 weeks. Participants were asked to practice at home on nonclass d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…All components of our defined feasibility measures were met. All nine participants were able to log in and successfully attend at least one class by VVC and five of the nine attended 11 or more virtual classes out of the 16 taught over an 8-week period (median [interquartile range]: 11 [4][5][6][7][8][9][10][11][12][13][14][15]). Two spouses attended on a regular basis, as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All components of our defined feasibility measures were met. All nine participants were able to log in and successfully attend at least one class by VVC and five of the nine attended 11 or more virtual classes out of the 16 taught over an 8-week period (median [interquartile range]: 11 [4][5][6][7][8][9][10][11][12][13][14][15]). Two spouses attended on a regular basis, as well.…”
Section: Resultsmentioning
confidence: 99%
“…Tai Chi meets these criteria 11 . When practiced regularly, Tai Chi appears to have benefits not only for balance, fitness, and flexibility but also for the relief of pain and depression 11–19 . Traditionally, Tai Chi classes are offered face‐to‐face in a group setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the promising data from younger adults [22,23], the value of TC for older adults with CNLBP remains worthy of investigation. Only two studies have looked at the role of TC in the elderly with CNLBP [24,25], but both have some limitations. Lee et al's study [24] demonstrated the multifaceted bene ts of TC for the elderly with CNLBP, but this study is only a qualitative study and the sample size is seriously insu cient (n = 18).…”
Section: Introductionmentioning
confidence: 99%
“…Only two studies have looked at the role of TC in the elderly with CNLBP [24,25], but both have some limitations. Lee et al's study [24] demonstrated the multifaceted bene ts of TC for the elderly with CNLBP, but this study is only a qualitative study and the sample size is seriously insu cient (n = 18). Sherman et al's study [25] con rmed that TC intervention is feasible and acceptable in the elderly with CNLBP, but in terms of sample size, it has the same methodological problems as an above study.…”
Section: Introductionmentioning
confidence: 99%